ANALYSIS OF SEA SURFACE CONDITIONS DURING ROB FLOOD EVENTS USING HYDRODYNAMIC MODELS IN MAKASSAR CITY (CASE STUDY: DECEMBER 24, 2022) - Taqwim, Muhammad Ahsani; Asbar, Asbar; Asni, Andi; Mahagnyana, Mahagnyana (Politeknik Kelautan dan Perikanan Dumai, 2025)
The coastal flooding (ROB) event that occured on Barrang Lompo Island, Sangkarrang District, Makassar City on December 24, 2022.